Rho Kinase (ROCK) Inhibitors - Liao, James K. (2007)
The Rho kinase (ROCK) isoforms, ROCK1 and ROCK2, were initially discovered as downstream targets of the small GTP-binding protein Rho. Because ROCKs mediate various important cellular functions such as cell shape, motility, secretion, proliferation, and gene expression, it is likely that this pathway will intersect with other signaling pathways known to contribute to cardiovascular disease. Indeed, ROCKs have already been implicated in the regulation of vascular tone, proliferation, inflammation, and oxidative stress. However, it is not entirely clear how ROCKs are regulated, what some of their downstream targets are, and whether ROCK1 and ROCK2 mediate different cellular functions. Clinically, inhibition of ROCK pathway is believed to contribute to some of the cardiovascular benefits of statin therapy that are independent of lipid lowering (ie, pleiotropic effects). To what extent ROCK activity is inhibited in patients on statin therapy is not known, but it may have important clinical implications. Indeed, several pharmaceutical companies are already actively engaged in the development of ROCK inhibitors as the next generation of therapeutic agents for cardiovascular disease because evidence from animal studies suggests the potential involvement of ROCK in hypertension and atherosclerosis.